Endurance training in MS: short-term immune responses and their relation to cardiorespiratory fitness, health-related quality of life, and fatigue - Bansi, J.; Bloch, W.; Gamper, U.; Riedel, S.; Kesselring, J. (Journal of neurology, 2013)
The influences of exercise on cytokine response, health-related quality of life (HR-QoL), and fatigue are important aspects of MS rehabilitation. Physical exercises performed within these programs are often practiced in water, but the effects of immersion have not been investigated. To investigate the influences of short-term immune responses and cardiorespiratory fitness on HR-QoL and fatigue during 3 weeks endurance training conducted on a cycle-ergometer or an aquatic-bike. Randomized controlled clinical trial in 60 MS patients. HR-QoL, fatigue, cardiorespiratory fitness, and short-term immune changes (serum concentrations in response to cardiopulmonary exercise test) of brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), interleukin-6, and the soluble receptor of IL-6 (sIL-6R) were determined at the beginning and end of 3 weeks of training intervention. Subjects performed daily 30 min training at 60 % of their VO2peak. SF-36 total ( p = 0.031), physical ( p = 0.004), and mental health ( p = 0.057) scores show time effects within both groups. Between-group effects were shown for FSMC total ( p = 0.040) and motor function score ( p = 0.041). MFIS physical fatigue showed time effects ( p = 0.008) for both groups. Linear regression models showed relationships between short-term immune responses and cardiorespiratory fitness with HR-QoL and fatigue after the intervention. This study indicates beneficial effects of endurance training independent of the training setting. Short-term immune adaptations and cardiorespiratory fitness have the potential to influence HR-QoL and fatigue in persons with MS. The specific immune responses of immersion to exercise need further clarification.